Recent advances on thermally conductive adhesive in electronic packaging: A review - Alim M.D.; Abdullah M.Z.; Aziz M.S.A.; Kamarudin R.; Gunnasegaran P. (MDPI, 2023)
Adhesives; Electronics packaging; Fillers; Nanocomposites; Nanoparticles; Temperature control; Bonding strength; Conductive fillers; Electronic Packaging; Epoxy adhesives; Epoxy-based; Nano composite; Thermal; Thermally conductive adhesive; Thermally conductive adhesives; Thermal conductivity